Education for transgression: Narratives of “barrier-free” individuals on family and school determinants of exceeding one’s own limitations - Cierpiałowska, Tamara (Multidisciplinary Journal of School Education, 2025)
Research objectives and problem: The aim of this article is to analyze determinants related to family and school that foster exceeding one’s own limitations (transgression) in the narratives of “barrier-free” individuals. The research question is formulated as follows: Which factors that contribute to readiness for transgressive action and are associated with the family and educational environment emerge in autobiographical reconstructions? The analysis identifies conditions that are conducive to transgression. Reflection on these factors may support the educational process and, through biography-based learning, be used in formative practice. Research methods: Empirically, the article draws on the authors’ qualitative study of people with disabilities who were finalists or laureates of the nationwide competition called “Person Without Barriers.” The study was conducted within the interpretive paradigm using the biographical method and procedures of grounded theory. Process of argumentation: Amid multiple contemporary crises, young people increasingly face isolation, loss of trust, diminished sense of meaning, and difficulties in setting life goals. The incidence of mood disorders, anxiety, and self-destructive behavior among children and adolescents is rising. This results in the need for effective forms of educational support. One possible form of action is education grounded in the life stories of “barrier-free” individuals. Theoretically, the article refers to psychotransgressionism and the notion of homo transgressivus, which were developed by the Polish psychologist Józef Kozielecki. Research findings and their impact on the development of educational sciences: The analysis indicates that family and school conditions are crucial for the development of transgressive action. The identified family factors were acceptance, granting age-appropriate autonomy and decision-making, cultivating a belief in one’s capabilities rather than focusing on deficits, fostering resourcefulness, and building optimism. School-related factors included treating the student as a subject/agent, setting demanding expectations, and simultaneously adopting individualized and flexible responses to the student’s needs and abilities. Conclusions and recommendations: The narratives of “barrier-free” individuals show that the identified features of the family and school environment support transgression. This knowledge should be disseminated among parents and teachers/educators, as a particular approach to upbringing can create opportunities for young people to move beyond various constraints and to formulate and attain ambitious life goals.